STRATEGI ADAPTASI PEREMPUAN TENGANAN PEGRINGSINGAN DALAM PEMBUATAN BANTEN DI TENGAH PUSARAN NEGOSIASI RUANG ADAT - Wilda Nurul Sukarno Putri (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2026)
This article explores the dynamics of adaptation and negotiation carried out by indigenous women in Tenganan Pegringsingan Village, Karangasem, Bali, in performing the tradition of banten (ritual offerings) making amid the pressures of modernity and the growing demand for efficiency. As one of the Bali Aga villages that strongly upholds awig-awig (customary law) in everyday life, the community of Tenganan Pegringsingan is often misperceived as a society that resists change. In reality, however, the villagers continuously encounter various transformations in social, economic, technological, and tourism dynamics that shape their daily lives. Based on ethnographic research employing participant observation, in-depth interviews, and literature review, this study demonstrates that customary practices in the village are not static. Tenganan women play a crucial role in reproducing as well as negotiating customary practices, particularly in the tradition of banten making, through various adaptive strategies in their daily lives. Utilizing the Practice Theory framework developed by Pierre Bourdieu, this article analyzes how women’s habitus that formed within a strong customary system, interacts with different forms of capital in responding to social change. The findings reveal that Tenganan women develop practical strategies such as collective labor-sharing through the practice of metulung and the selective use of more efficient materials, while maintaining the sacred boundaries defined by customary norms. Thus, adaptation in this context does not represent a dilution of tradition but rather constitutes a form of social practice that enables the continuity of banten making amid changing social conditions. The study further highlights that the sustainability of customary traditions in Tenganan Pegringsingan depends not only on the authority of awig-awig, but also on women’s agency in navigating and negotiating ritual practices in everyday life.